PENGARUH PRODUK DOMESTIK BRUTO, MONEY SUPPLY, DAN FOREIGN DIRECT INVESTMENT TERHADAP MARKET RETURN DI INDONESIA - B31111144, Andreas Gemelio Pungkar (Jurnal Manajemen Update, 2016)
This study analyzes the influence of the Gross Domestic Product, Money Suplly, as well as Foreign Direct Investment to Market Return. This topic began to attract attention since Stephen A. Ross ofÂ  M.I.T. (1976) developed an approach known as the Arbitrage Pricing Theory (APT) which is used to analyze the relationship between economic variables to capital markets in a country. Located in Indonesia, using quarterly data for 39 periods, as well as analytical tools Ordinary Least Square, this study found a significant effect of the Gross Domestic Product and Market returnt-1. Influence of Money Supply and Foreign Direct Investment was found not significant. On the other hand, the Gross Domestic Product and Money Supply (M2), when viewed by the regression coefficients, positive effect on the market return. Market returnt-1 as well as Foreign Direct Investment found to affect adversely the market return. These findings indicate the importance of macro variables as a basis for decision making. For investors, these findings remind them to always pay attention to macroeconomic conditions in investing activities they are doing so managed to get a profit margin as they had hoped. For companies, these findings remind management to pay attention to macroeconomic conditions that may affect their operational activities as an effort to raise funds through IPO. Ultimately, these findings also touched on the validity of the theory of APT as one of the approaches that can be done in analyzing the return of stocks and the overall market. Keyword : Gross Domestic Product; Money Suplly; Foreign Direct Investment; Market Return; Arbitrage Pricing Theory